Incidence and factors associated with poor libido in breeding buffalo bulls - KUMAR, AJEET; SINGH, JAGIR; DHALIWAL, G S; SINGH, PAWAN (The Indian Journal of Animal Sciences, 2011)
Studies were conducted to find out the incidence and associated factors with poor libido in breeding buffalo bulls. Association of testosterone level and semen quality with poor libido was also investigated. The results of incidence and associated factors with libido in breeding bulls were analyzed as very poor, poor and good. Scrotal circumference, testicular volume, semen volume and sperm concentration differed nonsignificantly between very poor, poor and good libido bulls. Individual sperm motility and livability were significantly lower and abnormal sperm were significantly higher in very poor and poor libido bulls. Wide variation in testosterone level (0.02 to 27ng/ml) with respect to libido was observed. It was concluded that almost one-fourth (23.7%) of the breeding buffalo bull population were affected with poor libido primarily associated with lameness, scrotal dermatitis and or wide scrotal neck. Semen quality and freezability were also poor in very poor and poor libido bulls. Testosterone level was not associated with poor libido.Â